Pharmacognostic, phytochemical and pharmacological activities of Ocimum kilimandscharicum Guerke - Shah, Revti R.; Ogale, Sunita; Makwana, Aakash B. (International Journal of Basic & Clinical Pharmacology, 2024)
The family Lamiaceae encompasses a diverse array of therapeutic plants, with the genus Ocimum being particularly esteemed. The plant known as Kapur Tulsi in India, Ocimum kilimandscharicum Guerke is a perennial woody shrub characterized by its essential oil, which predominantly contains camphor, along with linalool, limonene, eugenol, 1,8-cineole, and camphene. This review aims to provide current information on the taxonomy, botany, distribution, ethnomedicinal uses, phytochemistry, pharmacology, and toxicological profile of O. kilimandscharicum. The information presented was critically analyzed to understand the current research on this species and to explore potential future opportunities for this plant in pharmaceutical research. A comprehensive literature search was conducted and relevant information was collected through an extensive exploration of bibliographic databases, including Google Scholar, ScienceDirect, PubMed, Web of Science, Semantic Scholar, Europe PMC, and Scopus. The literature suggests that the plant contains a range of compounds that underpin its broad spectrum of pharmacological effects. These phytoconstituents have been widely employed in the treatment and management of numerous conditions. This review consolidates the latest information on its phytochemical and pharmacological activities, traditional applications, and scientific research. The review highlights the significant phytoconstituents of Ocimum kilimandscharicum Guerke and summarizes the evidence supporting its pharmacological potential. The findings suggest that the plant’s diverse compounds contribute to its extensive use in traditional medicine and underscore its potential for therapeutic applications in various diseases.